Evaluation of the Cancer Council NSW Eat It To Beat It Healthy Lunch Box Sessions: A short intervention to promote the intake of fruit and vegetables among families of primary school children in NSW Australia. (28th December 2017) - Mihrshahi, Seema; Foley, Bridget; Nguyen, Binh; Gander, Kristi; Tan, Nina; Hudson, Nayerra; Hughes, Clare; Hector, Debra; Bauman, Adrian
Abstract: Issue addressed: Children and adults in Australia are not eating the recommended amounts of fruits and vegetables. Our objective was to assess the effectiveness of a health promotion intervention to improve fruit and vegetable intake among primary school children and their families in NSW. Methods: The Cancer Council New South Wales Healthy Lunch Box sessions were a 25‐minute session delivered to parents of primary school‐aged children. The sessions provided information and resources about fruit and vegetables and healthy school lunch boxes. The evaluation is a quantitative uncontrolled pre‐post design. Data were collected using three questionnaires, pre‐intervention, 1 week post‐intervention and 6 months post‐intervention. Results: A total of 204 parents completed all three evaluation questionnaires to 6 months. Knowledge of recommended intakes and serving sizes of fruit and vegetables improved significantly after the intervention. There was an increase in parents reporting packing vegetables (often/always) in the child's lunch box at 1 week (47%) and 6 months post‐intervention (40%) compared to pre‐intervention (32%). The proportion of parents reporting that they were confident in packing a healthy lunch box increased from 45% pre‐intervention to 62% after the intervention. Conclusion: The Healthy Lunch Box sessions were effective in improving parental knowledge and practices related to fruit and vegetables and parental confidence with packing a healthy lunch box. So what?: This short intervention could be a useful component of a portfolio of interventions to support parents with knowledge and resources to pack a healthy lunch box for their children.